Efficiency of initiating cell adhesion in hydrodynamic flow - Korn, Christian B.; Schwarz, Ulrich S. (Arxiv, 2006)
We theoretically investigate the efficiency of initial binding between a receptor-coated sphere and a ligand-coated wall in linear shear flow. The mean first passage time for binding decreases monotonically with increasing shear rate. Above a saturation threshold of the order of a few 100 receptor patches, the binding efficiency is enhanced only weakly by increasing their number and size, but strongly by increasing their height. This explains why white blood cells in the blood flow adhere through receptor patches localized to the tips of microvilli, and why malaria-infected red blood cells form elevated receptor patches (knobs).